2020
DOI: 10.12806/v19/i3/a5
|View full text |Cite
|
Sign up to set email alerts
|

An Engaged Scholarship Approach to Create and Evaluate a Leadership Development Program for Students

Abstract: Expectations continue to evolve in today's work environment. An innovative practice between university and industry partners has emerged as a response to these expectations. In this trend, programs prepare college students with essential skills before entering the workforce. One such partnership created a leadership development program for workforce preparation using proven best practices and theories. The 70-20-10 framework, developed by researchers and authors working with the Center for Creative Leadership,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This research also highlights a potentially informative way to bring student voices to program evaluation. Student voices in program evaluation are both important and informative (Maldonado-Franzen, 2020). The use of student voices is an important component in program redesign and improvement (Paufler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This research also highlights a potentially informative way to bring student voices to program evaluation. Student voices in program evaluation are both important and informative (Maldonado-Franzen, 2020). The use of student voices is an important component in program redesign and improvement (Paufler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Whisler et al (2017) used the Value Creation process created by Wenger et al (2011) to re-design and assess an undergraduate peer tutoring program at Clemson University. Kirkpatrick’s (1994) four levels of training evaluation tool is used regularly in education (Franzen, 2020); nursing, (Ying et al, 2019), and banking (Drozdova & Guseva, 2017). While the intent is similar, the focus and terms may differ (Edmondson, 2011).…”
Section: Program Assessmentmentioning
confidence: 99%
“…Scholarship policies have a significant influence on the development of a nation, especially in improving the quality of human resources and access to quality education (Ilechukwu, 2014;Sari, 2023). Various studies have shown how scholarship programs contribute socially and economically (Gufron, Simanjuntak, & Novianti, 2022;Hilal, Scott, & Maadad, 2015) or can even become a potential model for building the leadership capacity of the nation's young generation (Franzen, 2020). For this reason, capacity building and quality of human resources, which in this research is pursued through a scholarship policy, can be the prime capital for national development.…”
Section: Introductionmentioning
confidence: 99%